Impact of monthly headache days on anxiety, depression and disability in migraine patients: results from the Spanish Atlas - P. Irimia (Nature Portfolio, 2021)
Abstract Identifying highly disabled patients or at high risk of psychiatric comorbidity is crucial for migraine management. The burden of migraine increases with headache frequency, but the number of headache days (HDs) per month after which disability becomes severe or the risk of anxiety and depression is higher has not been established. Here, we estimate the number of HDs per month after which migraine is associated with higher risk of anxiety and depression, severe disability and lower quality of life. We analysed 468 migraine patients (mean age 36.8 ± 10.7; 90.2% female), of whom 38.5% had ≥ 15 HDs per month. Our results show a positive linear correlation between the number of HDs per month and the risk of anxiety (r = 0.273; p < 0.001), depression (r = 0.337; p < 0.001) and severe disability (r = 0.519; p < 0.001). The risk of anxiety is higher in patients having ≥ 3HDs per month, and those with ≥ 19HDs per month are at risk of depression. Moreover, patients suffering ≥ 10HDs per month have very severe disability. Our results suggest that migraine patients with ≥ 10HDs per month are very disabled and also that those with ≥ 3HDs per month should be screened for anxiety.